Circular RNA circSIPA1L1 Contributes to Osteosarcoma Progression Through the miR-411-5p/RAB9A Signaling Pathway - Xu, Yining; Yao, Teng; Ni, Haonan; Zheng, Rujie; Huang, Kangmao; Huang, Yizhen; Gao, Jun; Qiao, Di; Shen, Shuying; Ma, Jianjun (Frontiers in Cell and Developmental Biology, 2021)
Recently, various studies have identified circular RNAs (circRNAs) to play a significant role in tumorigenesis, thereby showing potential as novel tumor biomarkers. circSIPA1L1 is a new-found circular RNA formed by back-splicing of SIPA1L1 and is found increased in osteosarcoma (OS). Nevertheless, the specific functions of circSIPA1L1 in OS remain unknown. In the present study, circSIPA1L1 was obtained from a previously reported circRNA microarray in the GEO database (GSE96964). Quantitative real-time polymerase chain reaction (qRT-PCR) was employed to assess the mRNA level of circSIPA1L1 in OS cell lines and tissue samples. Bioinformatics analysis, luciferase reporter assays, real-time PCR, RNA pull-down assays and RNA immunoprecipitation (RIP) were employed to verify the binding of circSIPA1L1 with miR-411-5p. Xenograft tumor models were established to identify the role of circSIPA1L1 in vivo. A series of in-vitro experiments, such as western blotting , colony formation, transwell assays and anoikis assay were employed to confirm the relationship across circSIPA1L1, miR-411-5p, and RAB9A. Our study confirmed circSIPA1L1 to be upregulated in both human OS samples and OS cell lines. Mechanistically, circSIPA1L1 could serve as a miR-411-5p molecular sponge to increase RAB9A expression, which was confirmed to be a tumor promoter mediating carcinogenesis. Silencing of circSIPA1L1 attenuated the vitality, invasion, migration and proliferation of OS cell lines both in vivo and in vitro. miR-411-5p inhibition or RAB9A overexpression reversed the anti-tumor effects caused by circSIPA1L1 knockdown. Briefly, circSIPA1L1 acts as a driver gene in OS and could initiate OS tumorigenesis through the miR-411-5p/RAB9A signaling pathway, which might become a potential therapeutic biomarker for OS treatment.